DEVELOPMENT OF ENTREPRENEURIAL SUSTAINABILITY FOR ALUMNI STUDENTS - Indah Wahyu Utami; Indra Hastuti; Sharina Osman; Singgih Purnomo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Entrepreneurial development after graduating from college is very necessary for students so that businesses or businesses run by dapat are developed in a sustainable manner. Students after graduating college on average look for work and do not continue their efforts. The problem in student business is limited labor, timely service, still limited in the use of information technology in marketing and business premises or business. This makes the student's business or the business is unsustainable. The goal of this activity is to assist in the management and development of businesses run by students who have advantages and are capable of creating jobs and trying to assist the government in its efforts to reduce joblessness. Entrepreneurial development's outcomes activities produced by 6 (six) Indonesian students after graduating from college can continue and develop their business. Keywords : development, entrepreneurship, student, sustainable